Improving air monitoring system in the city - L. O. Shtripling; V. V. Bazhenov; N. S. Bazhenova; P. E. Nor (Омский научный вестник)
Despite the fact that the majority of large industrial enterprises in Omsk comply with environmental legislation, the problem of air pollution is acute in the city. The expansion of the network of air pollution observation posts allows us to improve the quality of determining background pollution, but it is not able to answer the question of who is to blame for excess air pollution. The article presents the development aimed at improving the existing monitoring system, which allows, on the one hand, to determine the level of pollution at any point in the area, and, on the other hand, to quickly respond to complaints from the population about the violation of atmospheric air quality and identify sources of excess emissions in the city.